2015
DOI: 10.1007/s11515-015-1348-0
|View full text |Cite
|
Sign up to set email alerts
|

High on food: the interaction between the neural circuits for feeding and for reward

Abstract: Hunger, mostly initiated by a deficiency in energy, induces food seeking and intake. However, the drive toward food is not only regulated by physiological needs, but is motivated by the pleasure derived from ingestion of food, in particular palatable foods. Therefore, feeding is viewed as an adaptive motivated behavior that involves integrated communication between homeostatic feeding circuits and reward circuits. The initiation and termination of a feeding episode are instructed by a variety of neuronal signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 134 publications
(176 reference statements)
0
21
0
Order By: Relevance
“…Leptin suppresses excitatory synaptic drive onto LHA-to-VTA-projecting orexin and MCH neurons We used an established retrograde tracing approach (Katz et al, 1984;Köbbert et al, 2000;Lammel et al, 2008;Brown and Hestrin, 2009) to label LHA neurons forming synapses within the VTA. Briefly, we injected microfluorescent RetroBeads into the VTA and identified retrograde labeled neuronal cell bodies in the LHA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin suppresses excitatory synaptic drive onto LHA-to-VTA-projecting orexin and MCH neurons We used an established retrograde tracing approach (Katz et al, 1984;Köbbert et al, 2000;Lammel et al, 2008;Brown and Hestrin, 2009) to label LHA neurons forming synapses within the VTA. Briefly, we injected microfluorescent RetroBeads into the VTA and identified retrograde labeled neuronal cell bodies in the LHA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The LHA has been recognized as a "feeding center" and is positioned to integrate energy status and metabolic signals to control food intake (Hoebel and Teitelbaum, 1962;Grossman et al, 1978;Jennings et al, 2013;Sheng et al, 2014). It is well established that LHA neurons are major targets for central leptin signaling (Leinninger et al, 2009(Leinninger et al, , 2011Domingos et al, 2013;Goforth et al, 2014;Laque et al, 2015), and it has been suggested that they may play a role in regulating the reward-associated ventral tegmental area (VTA) dopaminergic (DA) signaling and reward (Harris et al, 2005;Borgland et al, 2006;Narita et al, 2006;Leinninger et al, 2009;Domingos et al, 2013;Sheng et al, 2014). However, the complex wiring pattern and neuronal heterogeneity of the LHA (Liu et al, 2015;Mickelsen et al, 2017) has complicated the discovery of precise neural mechanisms mediating leptin function.…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding behavior is ultimately determined by a complex interaction between the two (Liu et al, 2015). Hedonic eating has become a key cause of weight gain and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a pressing need to further investigate the role of reward circuitry in the regulation of feeding behavior (Volkow et al, 2011). The neural circuits governing food intake intertwine with those mediating reward, and the midbrain dopaminergic (DA) system has been suggested to play a pivotal role in the regulation of reward-related behaviors, including eating (Liu et al, 2015; Volkow et al, 2011). Several studies report that pharmacologic manipulations of GLP-1 signaling, i.e., using GLP-1 analogue Exendin 4 (Exn4) or GLP-1R blocker Exendin 9 (Exn9) infusions, in the VTA (Dickson et al, 2012; Mietlicki-Baase et al, 2013), NAc (Alhadeff et al, 2012; Dossat et al, 2013; Dossat et al, 2011), NTS (Alhadeff and Grill, 2014) and the hippocampus (Hsu et al, 2015), affect the appetitive and motivational aspects of feeding.…”
Section: Introductionmentioning
confidence: 99%